Perancangan Modul dan Video Pelatihan Gaya Komunikasi Supervisor PT. X - Gabriela Yohana (Jurnal Titra, 2022)
Modules and videos are materials that can be used for training, which allows participants to learn independently. PT. X desires to design training modules and videos about communication styles so that supervisors can learn independently and mitigate offline training. The purpose of this study is to design modules and videos about communication styles for supervisor. These training modules and videos are designed based on analysis of communication style of supervisor and Heffner’s main communication styles theories. The main communication styles consist of passive, aggressive, and assertive. The ideal communication style is assertive, whereas passive and aggressive communication style are usable in certain situations. The analysis was conducted based on viewpoints of the leader and staff. The analysis results shows that supervisor have an assertive communication style, so it’s ideal and must be maintained consistently. The modules and videos designed are in accordance with the characteristics of training modules and videos, and have been validated by the company.